Dynamic capabilities: The role of board monitoring and managerial incentives - Aman Asija; Dimo Ringov (BRQ Business Research Quarterly, 2021)
Research on the nature and value of firms' dynamic capabilities has produced contradictory propositions and findings. Scholars have argued that contingency theorizing has the potential to improve our understanding, as the context in which dynamic capabilities are deployed may affect their value. Drawing on agency theory, we propose that corporate governance mechanisms play a significant role in determining the value of firms' dynamic capabilities. In particular, we develop theoretical propositions about the differential effect of two corporate governance mechanisms-board monitoring and managerial incentives-on the value of dynamic capabilities in the form of complex codified routines, on one hand, and simple rules, on the other hand, at different levels of environmental dynamism.
Keywords: L21; L22; D80; G34; 650; Dynamic capabilities; agency theory; corporate governance; environmental dynamism